Condyle‐glenoid fossa relationship after Herbst appliance treatment during two stages of craniofacial skeletal maturation: A retrospective study. (3rd September 2019) - Cheib Vilefort, Paula Loureiro; Farah, Leticia Orefice; Gontijo, Henrique Pársia; Moro, Alexandre; Ruellas, Antonio Carlos de Oliveira; Cevidanes, Lucia Helena Soares; Nguyen, Tung; Franchi, Lorenzo; McNamara, James A.; Souki, Bernardo Quiroga
Abstract: Objectives: To perform a three‐dimensional evaluation of the position of the condyles in patients treated with Herbst appliance (HA) in two stages of cervical vertebral maturation. Setting and sample population: Retrospective case‐control study. Pubertal Herbst group (PHG; n = 24, mean age 14.5 years, CS 3 and CS 4) and pre‐pubertal Herbst group (PPHG; n = 17, mean age 9.9 years, CS 1 and CS 2) were contrasted with comparison groups of non‐orthopaedically treated Class II patients in pubertal (PCG; n = 17, mean age 13.9 years) and pre‐pubertal maturational stages (PPCG; n = 18, mean age 10.6 years). Materials and Methods: Cone‐beam computer tomography scans were taken before treatment (T0) and at T1 after 8 to 12 months. Point‐to‐point measurements of the displacement of the condyles between T0 and T1, relative to the glenoid fossae, were performed in the X, Y, Z and 3D perspectives. Qualitative assessments using semi‐transparent overlays and colour mapping also were produced. Results: The displacement of the condyles within the glenoid fossae in the treated groups was small (<0.75 mm; P > . 05). Relative to the glenoid fossa, condylar position at T1 was similar to T0 in pre‐pubertal and pubertal groups ( P > . 05). Similar condylar rotations from T0 to T1 were observed in Herbst and comparison groups, and no significant difference was found between pre‐pubertal and pubertal patients. Conclusions: Regardless the stage of skeletal maturation, HA treatment did not change the condyle‐glenoid fossa relationship.